Willa and Wade. 2, The museum of Willa and Wade - Henderson, Judith (Henderson, Judith. Willa and Wade, 2025)
"Willa and Wade (an ostrich and a penguin) discover something curious on their walk. The small round object is sparkly but looks veryold. They've discovered a treasure--and it belongs in a museum. In fact, it belongs in their very own museum, which will be called the Museum of Willa and Wade (MOWW). So, how do you make a museum? Well,first they have to choose a location. A box labeled MOWW is just the thing. Next, they need to add a few more treasures. Wade's rock, handed down for generations, and Willa's dinosaur are perfect for rounding out the collection. Add a cafeâ and a grand opening and voiláa! They've created the perfect museum--almost as perfect as their friendship"--